HUMANITARIAN INTERVENTION IN AFRICA: TOWARDS A NEW POSTURE - Gueli, Richard (Scientia Militaria - South African Journal of Military Studies, 2012)
‘Throughout history it has been the inaction of those who could have acted, the indifference of those who should have known better, the silence of the voice of justice, that has made it possible for evil to triumph.’ - Emperor Haile Selassie of Ethiopia.1. IntroductionArticle 2 of the Charter of the United Nations (UN) implicitly recognises the validity of the concept of non-intervention, when it articulates ‘nothing contained in the present Charter shall authorise the [UN] to intervene in matters which are essentially within the domestic jurisdiction of any state’.1 This principle has been designed to reassure member states of the UN that their sovereign rights are respected, and that they should never become targets of intervention.2 If this is indeed the case, why then bother with the notion of intervention?